2010
DOI: 10.1016/j.jfludis.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Overreliance on auditory feedback may lead to sound/syllable repetitions: Simulations of stuttering and fluency-inducing conditions with a neural model of speech production

Abstract: This paper investigates the hypothesis that stuttering may result in part from impaired readout of feedforward control of speech, which forces persons who stutter (PWS) to produce speech with a motor strategy that is weighted too much toward auditory feedback control. Over-reliance on feedback control leads to production errors which, if they grow large enough, can cause the motor system to "reset" and repeat the current syllable. This hypothesis is investigated using computer simulations of a "neurally impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
168
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 172 publications
(343 reference statements)
15
168
3
2
Order By: Relevance
“…The stronger response to altered auditory feedback in the ramp phase is at least partially consistent with an overreliance on auditory feedback, another model discussed earlier. This interpretation corresponds to neurocomputational models showing that stuttering, reported to share characteristics with DD (Malek et al, 2013), is characterized by a bias toward feedback control (Civier et al, 2010). This overreliance, however, on auditory feedback could also not explain the weak de-adaptation in DD in the aftereffect phase.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The stronger response to altered auditory feedback in the ramp phase is at least partially consistent with an overreliance on auditory feedback, another model discussed earlier. This interpretation corresponds to neurocomputational models showing that stuttering, reported to share characteristics with DD (Malek et al, 2013), is characterized by a bias toward feedback control (Civier et al, 2010). This overreliance, however, on auditory feedback could also not explain the weak de-adaptation in DD in the aftereffect phase.…”
Section: Discussionsupporting
confidence: 76%
“…Studies on these formant adaptation effects in clinical disorders are scarce. Using simulations, Civier, Tasko, and Guenther (2010) showed that stuttering may be caused by deficits in speech feed-forward and feedback mechanisms (as explicated in the Directions Into Velocities of Articulators model). Their study suggests that stutterers rely too heavily on the auditory feedback trace to control speech and hence are more sensitive to changes in auditory feedback.…”
Section: Phonological Representations and The Role Of Altered Auditormentioning
confidence: 99%
See 1 more Smart Citation
“…The central nervous system of CWS-Per, on average, may exhibit increased levels of neuromotor noise compared to CWS-Rec and CWNS, resulting in difficulty using sensory information to optimally execute a motor plan (Wolpert, 2007). Stuttering has been associated with limitations in sensorimotor integration (Hickok, Houde, & Rong, 2011;Max, 2004;Max, Guenther, Gracco, Ghosh, & Wallace, 2004;Namasivayam & van Lieshout, 2011), including a deficit in the use of feedforward processing during speech (Cai et al, 2012;Civier, Tasko, & Guenther, 2010).…”
Section: Persistence Of Stuttering At 5-7 Years Of Age Is Associated mentioning
confidence: 99%
“…267-268). Likewise, results of a computer simulation study suggest that increased stuttering is associated with overmonitoring or "too much attention" (Civier, Tasko, & Guenther, 2010). Although several investigators have studied the relation between attention and stuttering behaviors (e.g., frequency of disfluencies) in adults who do and do not stutter (e.g., Arends, Povel, & Kolk, 1988;Bosshardt, 2002;Bosshardt, Ballmer, & de Nil, 2002;Oomen & Postma, 2001;Vasiç & Wijnen, 2001), to our knowledge only two studies have empirically assessed the relation between attention and stuttering behaviors in preschool-age children (Kraft et al, 2014;Ntourou et al, 2013).…”
Section: Attention and Childhood Stutteringmentioning
confidence: 99%